Designing of research coalitions in promoting GEOSS. A brief overview of the literature - Christine Heumesser (Universität für Bodenkultur Wien, Department für Wirtschafts- und Sozialwissenschaften, Institut für nachhaltige Wirtschaftsentwicklung, 2008)
The Global Earth Observation System of Systems (GEOSS) links a variety of existing and future observation systems and forecasting models into one comprehensive system of systems to provide accurate environmental data and to enable an encompassing vision and understanding of the Earth system. GEOSS is based on voluntary efforts, and shall be made accessible freely or at a very low cost, such that it bears properties of non-rivalry and non-excludability and can be compared with a public good. Agreements on the provision of a public good often suffer low participation. We apply a game theoretical approach to analyze GEOSS as a research coalition with varying spillover rates, in order to figure out whether a coalition with full participation can exist in equilibrium. We also focus on the question how varying spillover rates influence the size of the equilibrium coalition and suggest two measures, which can increase participation in equilibrium. The revision of the literature shows that the full participation is socially optimal and spillovers which take the form of strategic complements can lead to a high level of cooperation. Also measures like the linkage of negotiations and the formation of multiple coalitions can achieve a high level of participation.
Keywords: C72; H41; D70; 330; coalition theory; research coalitions; public goods